Cultural identification of entrepreneurship competency through Tampan Tailor film based on multimodality perspective - Rustono Farady, Marta; Benedicta Prihatin, Dwi Riyanti; Angela Oktavia Suryani; Harry; Sandroto, Christine Winstinindah; Wikantiyoso, Bimo (Penerbit Universiti Kebangsaan Malaysia, 2022)
Tracing the life story of an entrepreneur, many ups and downs occur and are difficult to map in detail, but their track record can be clearly illustrated through the medium of film. This research aims to map out the key visuals through the scenes of Tampan Tailor, as one of the films that promoted entrepreneurship in Indonesia, through multimodality. Multimodality research will use the mixture of Cultural Performance Theory by Victor Turner and 13 Indicators of Entrepreneurship Competency by Spencer & Spencer in order to map the key elements of the film scenes. This research relies on a qualitative approach with Multimodality Discourse Analysis by O’Halloran. The visual data collected in the research shows that entrepreneurship capabilities comes from the hardships the character faced along the story, even though the character does not contribute directly to tailoring business for the first half of the film. This is strengthened by financial condition of the character and his daily life to develop his entrepreneurial skills. Commitment, Perseverance, High Performance Focus and Opportunity are the key factors to develop entrepreneur’s competency as displayed in Tampan Tailor film. Throughout the visual scenes in the film, the audience can identify how the main character develops his soft and hard skills necessary to become a quality entrepreneur. It can be concluded from this research that there are numerous ways to express how entrepreneurial skills should be developed. These skills can develop not only in their field of expertise, but also outside their field which highlights the importance of working experience in order to become an entrepreneur.